ANTHROPOCENE: THE NEW HUMAN ERA AND THE CIRCULAR ECONOMY - de Giorge Cerqueira, Homero (2024)
This article aims to recognize the Anthropocene as the era of the new human, as well as to identify the circular economy as a business model of the future. In this study, the principles of the circular economy, theories and models of circular management, and the concepts of circular economy in its actions are explained in their specificity. As a methodology, this article involves a qualitative, descriptive research, with the realization of a documentary research, through the analysis of documents, as well as bibliographical research in national and foreign doctrine, in order to cross-reference the data for interpretation, substantiating the study.